Estudo de interações proteicas da Tiorredoxina Peroxidase Nuclear (nTPx) de Sacharomyces cerevisiae nos eventos de crescimento celular e silenciamento telomérico - Breyer, Carlos Alexandre (Universidade Federal de São Carlos, 2011)
The thioredoxin peroxidase (Tpx) is a group of antioxidant proteins that has been widely studied due to its role in the decomposition of different peroxides such as H2O2, peroxynitrite and organic peroxides. The ability of peroxide decomposition by Tpx is related to the presence of a conserved cysteine called peroxidatic cysteine (CysP). Most Tpx has a second cysteine (resolving cysteine - CysR) which forms a disulfide with CysP after peroxide decomposition. In addition to the peroxidase activity, some Tpx have molecular chaperone activity and are also involved in signaling of cell growth induced by hydroperoxides. It has been demonstrated that the Tpx cytosolic isoform of Schizosaccharomyces pombe is able to interact directly with MAPK (Sty1) via mixed disulfide, which is stabilized when the CysR is replaced by a serine residue. Saccharomyces cerevisiae have a nuclear isoform of Tpx (nTPx) and review of the literature shows the importance of this protein in maintaining the telomere silencing and decomposition of organic peroxides in the nucleus. Scale proteomic studies using mass spectrometry and two-hybrid indicate the nTPx association with MAP kinases. However, despite its location and participation in biological processes of relevance, works related to nTPx are scarce. Scale proteomics studies reported the physical interaction between nTPx and Mec3, Gts1, Pc1 and Dog2. These proteins are related to cell signaling or maintenance of telomeric silencing. However, no specific studies were performed to confirm these interactions and if they are established by mixed disulfides. This study aimed to evaluate the interactions previously described in the literature between nTPx and Mec3, Pcl1, Dog2 and Gts1 through the expression and purification of these proteins and in vitro evaluation of interactions as well as in vivo tests using two-hybrid. Several efforts were made with different approaches, nevertheless it was impossible overexpression of Mec3, Pcl1, Dog2, indicating a toxic effect of these proteins on the strains used. Furthermore, we found great success in overexpression of nTPx and nTpxC112S (8 mg and 10 mg per liter of cell culture) in Eschericchia coli strain BL21 (DE3) C43. This is the first time that these proteins were expressed in native form. It was also possible to overexpress the Gts1 protein in the same strain. These results could lead for new approaches in future studies in order to determine these threedimensional structures, by methods such as X-ray crystallography or nuclear magnetic resonance (NMR). Finally, the results obtainedusing the technique of two-hybrid yeast confirmed the interaction in vivo among nTPx and Mec3, Gts1, Dog2. However, opposing the results described in the literature, no interaction was detected between nTPx and PCL1, emphasizing the necessity of specific experiments in addition to the large-scale ones.
Keywords: Biotecnologia; Saccharomyces cerevisiae; Células - crescimento; Silenciamento telomérico; Tiorredoxinas peroxidases; Thioredoxin Peroxidase; Cell Growth; Telomeric silencing; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS